Academic Leadership of Faculty Members in the Faculty of Media and Communication of Haikou University of Economics - Wanze , Li; Boonmepipit, Piyanart (Academic Journal of Rajapruk University, 2025)
Abstract The objectives of this research were 1. to study the academic leadership of faculty members in the Faculty of Media and Communication. 2. to compare the academic leadership of faculty members in the faculty of media and communication of Haikou University of Economics with different status of respondent classified by gender, age, education level, experience in university. The sample consisted of 40 faculty members by simple random sampling.The research instrument was a questionnaire with IOC values between .67-1.00 and a reliability value of .97. The data were analyzed by frequency, percentage, mean, standard deviation, t-test, One-way ANOVA, and LSD. The results of the research were as follows: 1) The academic leadership offaculty members in overall was at a highest level, When classified by aspect, They were found that 4 aspects were at the highest level could be arranged from highest to lowest value were Dimension of promoting positive and collaborative relationship with faculty members, Dimension of professional development of faculty members abilities, Dimension of setting goals and development and Dimension of assessment and monitoring of student academic performance and It was at a high level was Dimension of promoting external communication performance. 2) Results of comparing academic leadership of faculty members in the Faculty of Media and Communication of Haikou University of Economics found that: Gender were not different, Age were not different, Education level was overall not difference but the aspects was Dimension of professional development of faculty members’ abilities and Dimension of promoting external communication were difference at .05 significant and Experience in university were not different. Keywords: Academic leadership Faculty members Haikou University